Aktivitas Belajar Siswa Kelas V dalam Pembelajaran IPAS melalui Simulasi Erupsi Gunung Berapi dengan Model Project Based Learning - Dwi Loli Melani; Rara Auliya Dinastika; Murjainah Murjainah; Gian Handini (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to explain students' learning activities in Natural and Social Sciences (IPAS) subjects using a volcanic eruption simulation through the Project Based Learning (PjBL) model. The background of this study is the low student engagement caused by the teacher-oriented learning method, so that students tend to be passive. The method used in this study is descriptive qualitative, with data collection techniques in the form of observation, interviews, and documentation. The subjects of this study were fifth-grade elementary school students. The learning process was carried out through the PjBL stages, which include project planning, project implementation, and presentation of project results. In addition, this learning also contributes to improving the ability to work together, think critically, be creative, and solve problems. Contextual and experience-based learning helps students understand the material better and increases their motivation and curiosity. Thus, the PjBL model has proven effective in increasing student learning activities in science learning at the elementary school level.